Proximity and R&D Cooperation between firms: Location, R&D and Output in an Oligopoly with Spillovers - Isabel Mota; António Brand\~ao (European Regional Science Association (ERSA), 2004)
This paper aims at explaining how proximity between firms affects cooperation in R&D. For that purpose, it is proposed a three-stage game amongst three firms where each firm decides about location, R&D and output. Firms' decision about location determines a R&D spillover, which is inversely related to the distance between firms. R&D output is assumed to be cost reducing and exhibit diminishing returns. Cooperation is only allowed in the R&D stage. Our results allow us to conclude that there is a positive relationship between R&D output equilibrium and the distance between firms when firms act independently. When firms cooperate in R&D, R&D output for a cooperating firm increases with the degree of information sharing between them, as well as with a reduction of the distance between cooperating firms. Firms' decision about location is also affected by R&D activities: if R&D activities run independently, the clustering of firms only occurs for a convex spillover function; if R&D activities run cooperatively, clustering is always observed if there is an increased information sharing between firms. Keywords: Location, R&D cooperation, R&D spillovers
Keywords: 330; Location; R&D cooperation; R&D spillovers